1993
DOI: 10.1108/00242539310045426
|View full text |Cite
|
Sign up to set email alerts
|

Bibliographic Instruction for International Students in Academic Libraries

Abstract: Reviews the problems posed by international students in higher education in the USA, and some of the difficulties they encounter. Specifically relates these problems to the provision of library services and, more specifically, to bibliographic instruction. Reports on a survey from the University of Toledo to examine foreign students′ background knowledge of academic libraries and to develop a programme to meet the special needs of this multicultural group. Presents specific conclusions and recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The interactions with staff that emerged during interview also followed patterns identified in the literature (Robertson, 1992;Garcha & Russell, 1993 (as also highlighted in (Lu & Adkins, 2012)). Although Participant B stated that he approached staff in the library for help, it was clear that he was not taught how to find resources for himself: "they'll find the decimal number and then they'll tell me.…”
Section: Considerations For the University Library Servicementioning
confidence: 88%
See 1 more Smart Citation
“…The interactions with staff that emerged during interview also followed patterns identified in the literature (Robertson, 1992;Garcha & Russell, 1993 (as also highlighted in (Lu & Adkins, 2012)). Although Participant B stated that he approached staff in the library for help, it was clear that he was not taught how to find resources for himself: "they'll find the decimal number and then they'll tell me.…”
Section: Considerations For the University Library Servicementioning
confidence: 88%
“…International students may be particularly affected by a lack of understanding of academic library culture in the United Kingdom (Robertson, 1992). It has been suggested that previous experiences of different library cultures influence the expectations of international students in university libraries (Baron & Strout-Dapaz, 2001;Garcha & Russell, 1993). A study of fifteen international graduate students in the United States found affective barriers to be a particularly significant factor in their library use (Lu & Adkins, 2012).…”
Section: International Studentsmentioning
confidence: 99%
“…Depending on previous practices in libraries in their home country, discomfort at asking for research help may also be due to a student's perception that the librarian is either a gatekeeper who should not be disturbed, or a book-retriever/clerk who is to be directed to perform a specific task. This can be especially problematic during situations of both cross-cultural and cross-gender communication, in which a student may not understand the professional role of librarians and in which a (female) librarian may perceive that a (male) student's demanding behavior is due to a lack of respect (Garcha and Yates Russell, 1993). This discomfort on the part of students and the perception of disrespect on the part of librarians can result in a cycle of discomfort, anxiety, and continued misunderstandings on both sides.…”
Section: Barriers To Acculturationmentioning
confidence: 95%
“…These differences in learning expectations can be exacerbated when international students are confronted with a North American academic library, which may be intimidating and anxiety-inducing (Chapdelaine & Alexitch, 2004). North American academic libraries differ from those in other countriesparticularly in developing countries-in several significant ways, including breadth and currency of resources offered (Garcha & Yates Russell, 1993;Liestman, 2000); open access to library resources (Badke, 2002;Macdonald & Sarkodie-Mensah, 1988); the make-up and role of librarians and library staff (Garcha & Yates Russell, 1993;Helms, 1995;Liestman, 2000); and possibly technological barriers, including lack of online databases and classification systems, although this is disputed in the literature (Badke, 2002;Jackson, 2005;Jiao & Onwuegbuzie, 2001).…”
Section: Barriers To Acculturationmentioning
confidence: 96%
“…Cultural differences can also affect communication. For instance, non-verbal signs can mean different things in different cultures (Wayman, 1984;Ball and Mahony, 1987;Garcha and Russell, 1993;Natowitz, 1995)[5]; or international students might lack familiarity with native idioms and college slang, which can result in cultural misunderstandings (Lacina, 2002)[6]. Cultural differences incorporate educational differences; consequently, learning styles across educational systems can be very different.…”
Section: International Studentsmentioning
confidence: 99%